The Dose-Dependent Pleiotropic Effects of the UBB+1 Ubiquitin Mutant - Banasiak, Katarzyna; Szulc, Natalia A.; Pokrzywa, Wojciech (Frontiers in Molecular Biosciences, 2021)
The activity of the proteolytic machinery diminishes with age, leading to abnormal accumulation of aberrant proteins; furthermore, a decline in protein degradation capacity is associated with multiple age-related proteinopathies. Cellular proteostasis can be maintained via the removal of ubiquitin (Ub)-tagged damaged and redundant proteins by the ubiquitin-proteasome system (UPS). However, during aging, cells of the central nervous system (CNS) begin to express a frameshift-mutated Ub, UBB+1. Its accumulation disturbs proteasome-dependent protein turnover, leading to the formation of neurotoxic aggregates. On the other hand, a low level of UBB+1 improves stress resistance and extends lifespan. Here we summarize recent findings regarding the impact of UBB+1 on Ub signaling and neurodegeneration. We also review the molecular basis of how UBB+1 affects UPS components as well as its dose-dependent switch between cytoprotective and cytotoxic roles.